THE INFLUENCE OF DEVELOPMENT EFFECTIVENESS AND EDUCATION AND TRAINING QUALITY ON THE DRIVER’S TECHNICAL SKILLS OF PT XYZ IN JAKARTA - Francis Tantri; Aang Gunawan; Marthaleina Ruminda (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2015)
The objective of this research is to study the inluence of development effectiveness and education and training quality on the driver’s technical skills of PT XYZ in Jakarta. The method of research is a survey using Path Analysis. The respondents for this survey are 35 drivers selected by applying proportional random sampling technique. The results of this research show that: (1) the effectiveness of development directly inluencing the driver’s technical skills is 35.8%, (2) the quality of education and training directly inluencing the driver’s technical skills is 33.8%, and (3) the effectiveness of coaching directly inluencing the quality of education is 25.5% The study concludes that technical skills can be improved through effective development and the quality of education and training, and the quality of education and training can be enhanced through effective development as well.